Cultural Transformation of Andhap Asor in Islamic Boarding Schools: Communication Patterns and Behavioral Coaching - Heri Fadli Wahyudi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This research focuses on communication patterns and behavioral development in Sumenep Islamic boarding schools to maintain local Madurese culture, especially Andhep Asor culture, amidst globalization's influence, threatening to preserve this culture. This study aims to examine the form of communication patterns and behavioral coaching in Sumenep Islamic boarding schools. This research is qualitative in the field, with data collection techniques through observation, interviews, and documentation. This study found that the communication pattern combines circle and Bintang communication patterns by adjusting to the Madurese level learning taught. Second, the coaching stage is through the Theoretical Transfer stage as a stimulus, through continuous reinforcement (continue), and through the formation of the Andhap Asor environment. Third, the transformation of Andhap Asor culture in Islamic boarding schools uses material with Islamic characters as the primary reference and through habits designed to be accepted quickly by the surrounding community in its implementation.